2021
DOI: 10.3389/fonc.2021.704042
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Xenograft Models for Intrahepatic Cholangiocarcinoma and Their Application in Guiding Personalized Medicine

Abstract: BackgroundIntrahepatic cholangiocarcinoma (ICC) remains one of the most intractable malignancies. The development of effective drug treatments for ICC is seriously hampered by the lack of reliable tumor models. At present, patient derived xenograft (PDX) models prove to accurately reflect the genetic and biological diversity required to decipher tumor biology and therapeutic vulnerabilities. This study was designed to investigate the establishment and potential application of PDX models for guiding personalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Direct implantation of human primary tumor cells into immunodeficient mice was used to establish a PDX model [ 49 , 50 ], which showed morphology, histology and immunoreactivity similar to the tumor of the primary patient [ 51 ], making it an excellent model for testing antitumor drugs. Based on the PDX model, we assessed lenvatinib’s effectiveness in treating ICC, and the results were consistent with previous research findings [ 16 ]. Lenvatinib seems to inhibit the proliferation, migration, invasion, and EMT of ICC.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Direct implantation of human primary tumor cells into immunodeficient mice was used to establish a PDX model [ 49 , 50 ], which showed morphology, histology and immunoreactivity similar to the tumor of the primary patient [ 51 ], making it an excellent model for testing antitumor drugs. Based on the PDX model, we assessed lenvatinib’s effectiveness in treating ICC, and the results were consistent with previous research findings [ 16 ]. Lenvatinib seems to inhibit the proliferation, migration, invasion, and EMT of ICC.…”
Section: Discussionsupporting
confidence: 87%
“…For example, a study reported that the combination of a PD-1 inhibitor and lenvatinib was effective in the treatment of ICC bone metastasis [ 15 ]. An ICC patient-derived xenograft (PDX) model was also used to reveal the effect of lenvatinib [ 16 ]. However, its role and mechanism in ICC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, Mini-PDX models cannot simulate the tumor microenvironment and the generation of tumor vasculature, resulting in lower sensitivity to targeted drugs compared to cytotoxic drugs. Sorafenib and lenvatinib, as FDA-approved systemic therapies for HCC, showed similar treatment responses in HCC PDX models compared to the primary patients, indicating that PDX models are effective tools for predicting the response to targeted therapy (Tiao et al, 2016;Gao et al, 2021). In a retrospective analysis, comparing the treatment outcomes of 92 patients with advanced solid tumors with the sensitivity of the corresponding PDX models to the same drugs, the sensitivity and specificity of PDX drug screening were 96% and 70%, respectively, with a positive predictive value of 85% and a negative predictive value of 91% (Izumchenko et al, 2017).…”
Section: Patient-derived Xenograft (Pdx) Modelsmentioning
confidence: 98%